Knowledge, Attitude and Practice about Neonatal Jaundice among Mothers at a Tertiary Care Hospital: A Questionnaire-based Cross-sectional Study - Sankeerthana Kamani; GN Shreekrishna; MO Abhishek; Santosh T Soans (Indian Journal of Neonatal Medicine and Research, 2025)
Introduction: Neonatal jaundice, also known as hyperbilirubinaemia, is a commonly encountered clinical condition in the postnatal period due to the immaturity of an infant’s liver’s ability to metabolise bilirubin efficiently. Early detection and prompt intervention are necessary to reduce the risk of severe hyperbilirubinaemia and associated complications, such as kernicterus. Parents are more inclined to seek early medical attention if they have better knowledge and awareness, a positive outlook and are not influenced by antiquated sociocultural beliefs and practices. Aim: To study the knowledge, attitudes and practices of mothers regarding neonatal jaundice in a tertiary care hospital. Materials and Methods: This questionnaire-based cross-sectional study was conducted at Department of Paediatrics, A.J. Institute of Medical Sciences and Research Centre, Mangaluru, Karnataka, India. All 108 mothers admitted to the postnatal ward following delivery and those visiting the postnatal clinic in the tertiary care centre during one month in April 2023 were included. Data were gathered using a structured questionnaire, which evaluated the mothers’ knowledge, attitudes and practices. Demographics and categorical variables were described using frequencies and percentages. Results: Out of 108 mothers, the majority belonged to the 25-34 years age group. Most of the mothers had good knowledge about detecting jaundice and its possible causes. A total of 64 (59.3%) mothers reported that cost was a barrier to accessing healthcare. Despite this, the study showed that 82 (75.9%) of them would still visit the hospital for a check-up, suggesting an overall good attitude. Only 2 (1.9%) believed in home remedies as a treatment. Knowledge gaps regarding danger signs and complications of neonatal jaundice were noted. Conclusion: The present study indicates that mothers possess good knowledge, attitudes and practices regarding neonatal jaundice. Counselling the mothers and conducting awareness programmes for caregivers can help improve knowledge, leading to early detection and treatment.